Virtual champions. (Economist, 2006)
This article discusses growth in India's information technology (IT) industry. In 2006 three of India's six biggest companies were involved in IT. During the 1990s Indian IT grew exponentially on the relatively simplistic software work needed to fix the millennium computer bug. It then received a boost from the dotcom bust, which in many firms in America and elsewhere, caused information-technology budgets to be slashed, prompting more outsourcing to India.